Production and nutritional value of Urochloa brizantha grass subjected to organic and chemical fertilization - González-Hernández, Petra; Hernandez, Erika Andrea; Vázquez Aguilar, Diego; Silva-Martínez, Karla Lissette; Del Ángel Piña, Oscar; León-García, Elizabeth (Ecosistemas y Recursos Agropecuarios, 2025)
The objective of this study was to evaluate the effect of organic and chemical fertilization on the production and nutritional composition of Toledo grass (Urochloa brizantha). Four treatments were evaluated: no fertilization (NF), Biol with water (FBW), Biol (FB) and chemical fertilization (CF), which were applied every 21, 28 and 35 days of regrowth. Biomass samples were taken to estimate dry matter production and determine the content of crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin (LIG) and ash (CEN). The highest yields were observed in the FB and at 35 days of cutting with 2 407 and 2 624 kg ha-1 of DM, respectively. The nutritional content did not vary between the treatments or the ages evaluated, however, it was observed that average values in the FBW and FB were within the ranges required for cattle nutrition.